2016
DOI: 10.1186/s12878-016-0052-x
|View full text |Cite
|
Sign up to set email alerts
|

Generic and disease-specific quality of life among youth and young men with Hemophilia in Canada

Abstract: BackgroundThis study was undertaken to explore the longitudinal patterns of health-related quality of life (HRQoL) among youth and young adults with Hemophilia A (HA) over a 3-year period. This report presents the baseline characteristics of the study cohort.MethodsMales, 14 to 29 years of age, with predominantly severe HA were recruited from six treatment centres in Canada. Subjects completed a comprehensive survey. HRQoL was measured using: the CHO-KLAT2.0 (youth), Haemo-QoL-A (young adults) and the SF-36v2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 19 publications
4
33
1
1
Order By: Relevance
“…SF-36 also allows comparison with normal population or with groups with other diagnoses. In our cohort, the PCS and MCS summary scores of SF-36v2 varied minimally from baseline to the end of study and were similar to those reported at baseline in the larger CHeQoLS study (mean PCS 51.7 ± 6.5, mean MCS 51.1 ± 8.6) [7]. This low variability could be explained by the fact that our subjects were already on a LDDP regimen at study entry, but also by the low number of subjects enrolled in our study.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…SF-36 also allows comparison with normal population or with groups with other diagnoses. In our cohort, the PCS and MCS summary scores of SF-36v2 varied minimally from baseline to the end of study and were similar to those reported at baseline in the larger CHeQoLS study (mean PCS 51.7 ± 6.5, mean MCS 51.1 ± 8.6) [7]. This low variability could be explained by the fact that our subjects were already on a LDDP regimen at study entry, but also by the low number of subjects enrolled in our study.…”
Section: Discussionsupporting
confidence: 78%
“…In addition, prophylaxis prevents bleeding and reduces the risk of life-threatening hemorrhages [10, 11, 18]. The purpose of our study was to describe clinical outcomes (bleeding rates and joint health), adherence to treatment and HRQoL in a cohort of patients treated on a LDDP regimen, while participating in a non-interventional and longitudinal study of youth and young adults with moderate or severe HA in Canada [7]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, we aimed to identify motivators to support patients' intrinsic desire to change their prophylaxis regimens, making increased infusion frequency less likely to be burdensome. Second, lack of difference in HRQoL in other studies may be due to small numbers, as the global HRQoL score is recognized to be insensitive to changes in patients with severe haemophilia compared to physical functioning or bodily pain subscales . Third, our patient population had a higher ABR and higher prevalence of joint disease at baseline compared to previous studies of daily prophylaxis; hence, they are more likely to derive a benefit in bleed reduction and improved HRQoL.…”
Section: Discussionmentioning
confidence: 99%